Direct Drive Simulation—Preoperative Sound Simulation of "Vibroplasty-Hearing" in Patients With Mixed Hearing Loss. Issue 4 (April 2020) - Kaulitz, Stefan; Großmann, Wilma; Steinbach, Julia; Hackenberg, Stephan; Mlynski, Robert; Rak, Kristen; Schraven, Sebastian Philipp; Hagen, Rudolf
Abstract : Objective: Validation of the preoperative sound simulation test for vibroplasty-hearing so-called "Direct Drive Simulation" (DDS) in case of mixed hearing loss. Study Design: Retrospective data analysis. Setting: Tertiary referral center with a large hearing implant program. Main Outcome Measure: Comparison of sound impression during preoperative Direct Drive Simulation, and postoperative testing with the activated active middle ear implant (AMEI) under free-field condition and in daily routine. Patients: Fifty-four data sets from 18 patients with mixed hearing loss with a mean age of 60.78 ± 3.18 were included. Results: Comparing the sound impression during DDS preoperatively versus free-field testing with the implanted AMEI, no significant differences were found. DDS offers a slightly better sound quality than the AMEI in daily routine, fitting well to the ideal listening situation in DDS versus some background noise in daily routine. Conclusion: The DDS offers the possibility of a realistic preoperative sound simulation of the "vibroplasty-hearing" in cases of mixed hearing loss. This probably facilitates patient's decision towards a vibroplasty. The audiologist as well as the surgeon get additional information regarding the indication especially when audiologic inclusion criteria are critical. Thus, the DDS is a useful extension of preoperative diagnostics before vibroplasty.